1981
DOI: 10.1002/pol.1981.170190226
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of ABA propylene‐ethylene block copolymers

Abstract: SynopsisExperimental data, which includes catalyst lifetimes, thermal analyses, fractionation by urea complexation, x-ray diffraction, and 13C-NMR spectroscopy, are presented to confirm the successful synthesis of ABA propylene-ethylene block copolymers. A dry catalyst system of DEAC-TiC13(AA) and a gas-phase polymerization technique was used to prepare the copolymers. PRP-and ERE-type copolymers (P-isotactic polypropylene, E-polyethylene, and R-random propylene-ethylene copolymer block) were prepared. Some pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In a living polymerization the rates of termination and chain transfer are negligible, relative to the rate of propagation . When these conditions are met, it is possible to attain polymer architectures such as block copolymers, star-shaped polymers, and end-functionalized polymers . Although reports of the living polymerization of olefins with transition metal catalysts can be traced to 1979, the majority of examples have been reported only within the past 5 years .…”
Section: Introductionmentioning
confidence: 99%
“…In a living polymerization the rates of termination and chain transfer are negligible, relative to the rate of propagation . When these conditions are met, it is possible to attain polymer architectures such as block copolymers, star-shaped polymers, and end-functionalized polymers . Although reports of the living polymerization of olefins with transition metal catalysts can be traced to 1979, the majority of examples have been reported only within the past 5 years .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the novel C­(sp 3 )–C­(sp 3 ) coupling reaction could be utilized for the construction of valuable ABA-type polyolefin triblock copolymers, which are expected to exhibit useful thermoplastic elastomer properties (Scheme ). Typically, the number-average molecular weight ( M n ) attainable in CCTP is limited (∼60 kDa). This work provides a method to prepare high molecular weight POs in CCTP and overcoming this limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Though the preparation of PP/PE blends by multi‐stage polymerization was reported many years ago,11 the toughness–stiffness balance of the material seems not to be attractive, and commercialization of this kind of polyolefin is quite limited compared to PP/EPR in‐reactor alloy (so‐called block PP or PP‐b). Chain structure and physical properties of propylene‐ethylene sequential polymerization products, which were prepared by using TiCl 3 ‐based catalysts, have been studied by several groups 12–16. As the PP and PE homopolymer chains were not separated from the block copolymer chains in these studies, the structure of the components of the studied polyolefins were not identified on solid experimental bases.…”
Section: Introductionmentioning
confidence: 99%